Helping Behavior and Joint Action in Young Children - Satne, Glenda Lucila (2015)
An important idea due to Tomasello and others is that the human capacity as the human capacity for social cooperation is at the heart of the species’ capacity to understand others’ mental states and behavior. Furthermore, they argue that this idea allows for an explanation of how humans came to share thoughts and language. While this is a promising idea, the special attempt to pursue this hypothesis in developmental studies and evolutionary theory developed by Tomasello and his research group faces several problems. This is especially apparent in their attempts to explain helping behavior and joint action in young children. In this paper, we argue that many of these problems result from assuming that the right explanation of joint action and simple forms of shared intentionality is given by Bratman’s theory of shared intentions.